Optogenetic Activation of Arcuate Kisspeptin Neurons Generates a Luteinizing Hormone Surge-Like Secretion in an Estradiol-Dependent Manner - Lin, Xian-Hua; Lass, Geffen; Kong, Ling-Si; Wang, Hui; Li, Xiao-Feng; Huang, He-Feng; O’Byrne, Kevin T. (Frontiers in Endocrinology, 2021)
Traditionally, the anteroventral periventricular (AVPV) nucleus has been the brain area associated with luteinising hormone (LH) surge secretion in rodents. However, the role of the other population of hypothalamic kisspeptin neurons, in the arcuate nucleus (ARC), has been less well characterised with respect to surge generation. Previous experiments have demonstrated ARC kisspeptin knockdown reduced the amplitude of LH surges, indicating that they have a role in surge amplification. The present study used an optogenetic approach to selectively stimulate ARC kisspeptin neurons and examine the effect on LH surges in mice with different hormonal administrations. LH level was monitored from 13:00 to 21:00 h, at 30-minute intervals. Intact Kiss-Cre female mice showed increased LH secretion during the stimulation period in addition to displaying a spontaneous LH surge around the time of lights off. In ovariectomized Kiss-Cre mice, optogenetic stimulation was followed by a surge-like secretion of LH immediately after the stimulation period. Ovariectomized Kiss-Cre mice with a low dose of 17β-estradiol (OVX+E) replacement displayed a surge-like increase in LH release during period of optic stimulation. No LH response to the optic stimulation was observed in OVX+E mice on the day of estradiol benzoate (EB) treatment (day 1). However, after administration of progesterone (day 2), all OVX+E+EB+P mice exhibited an LH surge during optic stimulation. A spontaneous LH surge also occurred in these mice at the expected time. Taken together, these results help to affirm the fact that ARC kisspeptin may have a novel amplificatory role in LH surge production, which is dependent on the gonadal steroid milieu.